PERUBAHAN TRADISI ERTUTUR DALAM ETIKA KEKERABATAN PADA MAHASISWA SUKU BATAK KARO DI KOTA PEKANBARU - Kiki Aprilya Ginting; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out how to change the tradition of Ertutur in kinship ethnic of students of Batak Karo students in Pekanbaru. This research uses a quantitative descriptive approach. As for the informant that is established by using the puprosive sampling technique, they are students of Batak Karo people who are taking a study in the city of Pekanbaru. Data collection techniques performed by observations, questionnaires, interviews and documentation. With primary and skunder data sources. Data analysis techniques by using combination method (Mix method). Based on the results of the research conducted, the researcher concluded that the tradition of Ertutur in kinship ethnic of students Batak Karo in Pekanbaru 54% already threaded refers to the average descriptive data of the alternative percentage answer